2021
DOI: 10.1111/acer.14542
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Exposure Attenuates Immune Response in Sepsis via Sirtuin 2 Expression

Abstract: Background Sepsis and septic shock kill over 270,000 patients per year in the United States. Sepsis transitions from a hyper‐inflammatory to a hypo‐inflammatory phase. Alcohol dependence is a risk factor for mortality from sepsis. Ethanol (EtOH) exposure impairs pathogen clearance through mechanisms that are not fully understood. Sirtuin 2 (SIRT2) interferes with pathogen clearance in immune cells but its role in the effects of EtOH on sepsis is unknown. We studied the effect of EtOH exposure on hyper‐ and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…influenzae , or E . coli ) as a challenge [ 32 , 36 , 40 42 , 65 , 79 , 86 ]; six used CLP model [ 36 , 38 , 39 , 76 , 78 , 82 ]; one used cecal slurry injection [ 83 ]; three studies used experimental colitis model [ 67 , 68 , 84 ]; one animal study used lipoteichoic acid [ 61 ]; one used 10–40 μg/mouse CpG DNA (TLR9 agonist) [ 63 ]; two used 500 nmole 1V136 or 20–100 μg R848 (TLR7 agonists), 25 μg/mouse Pam3CSK4 (TLR2 agonist), or 25 μg/mouse pIC (TLR3 agonist) [ 62 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…influenzae , or E . coli ) as a challenge [ 32 , 36 , 40 42 , 65 , 79 , 86 ]; six used CLP model [ 36 , 38 , 39 , 76 , 78 , 82 ]; one used cecal slurry injection [ 83 ]; three studies used experimental colitis model [ 67 , 68 , 84 ]; one animal study used lipoteichoic acid [ 61 ]; one used 10–40 μg/mouse CpG DNA (TLR9 agonist) [ 63 ]; two used 500 nmole 1V136 or 20–100 μg R848 (TLR7 agonists), 25 μg/mouse Pam3CSK4 (TLR2 agonist), or 25 μg/mouse pIC (TLR3 agonist) [ 62 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…All included human studies (12 studies) used LPS administration with in vivo doses of 2-4 ng/kg. Most animal studies (16 studies) used LPS administration with in vivo doses of 0.1-45 mg/kg in mouse or 2-400 μg/mouse via injection or 100 μg/mL via inhalation in mouse or 10 mg/lamb/injection, and with ex vivo doses of 1-1000 μg/mL; eight used treatments with bacteria (6000-10 7 colony-forming units (CFUs) of N. meningitidis, K. pneumoniae, S. pneumoniae, H. influenzae, or E. coli) as a challenge [32, 36, 40-42, 65, 79, 86]; six used CLP model [36,38,39,76,78,82]; one used cecal slurry injection [83]; three studies used experimental colitis model [67,68,84]; one animal study used lipoteichoic acid [61]; one used 10-40 μg/mouse CpG DNA (TLR9…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The role of SIRT2 in the immune response beyond cancer is also an interesting question. In general, SIRT2 has been shown to suppress the immune reaction in a variety of illnesses including sepsis 51 , chronic staphylococcal infection 52 , and tuberculosis 53 . Ethanol exposure increased SIRT2 expression and reduced the inflammatory response to sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis may increase the levels of IL-6 and TNF-α [4,15], damaging different organs [5,26] culminating in septic shock [22]. Increased levels of blood urea nitrogen and creatinine may occur during sepsis, important markers of kidney damage [4].…”
Section: Mechanisms Mediated By the Immune System In Ethanol Consumption And Sepsismentioning
confidence: 99%
“…Ethanol consumption directly affects immune function, leading to a decrease in the lymphocytic response, as well as alteration in cytokine production by lymphocytes and macrophages [15]. Other studies have demonstrated that the administration of ethanol suppresses the elimination of bacteria present in sepsis, with decreased pro-inflammatory chemokine levels (TNF-α and IL-6) [1,4,26]. The decrease in TNF-α itself may be responsible for the decreased recruitment of neutrophils, resulting in a less robust immune response [4].…”
Section: Mechanisms Mediated By the Immune System In Ethanol Consumption And Sepsismentioning
confidence: 99%